Language Qaedah, Interpretation Qaedah and Fikih Ushul in Mathematics Learning: Integration of Values, Logic and Knowledge Construction - Yossar; Nurhadi Ahmad; Nurnajmi; Elgusri; Mahyudin Ritonga; Mursal (Lembaga Bale Literasi, 2026)
This study discusses the integration of qaedah bahasa (linguistic rules), qaedah tafsir (principles of interpretation), and ushul fiqh (Islamic legal methodology) in mathematics learning. This integration approach has become important as awareness of the need for education that not only mastery of material but also forms character and systematic ways of thinking increases. The method used is a literature study with a qualitative-descriptive approach. The results of the study indicate three main positions: (1) the pro group who emphasizes that this integration enriches the meaning of mathematics learning and builds a holistic Islamic epistemology; (2) the contra group who worries about the imposition of values and the loss of mathematical objectivity; and (3) the intermediate group who offers a contextual and gradual integration model. These findings indicate that the success of integration is highly dependent on the availability of references, teacher training, and creativity in designing contextual examples with Islamic values.